Response of early maturing maize to multiplestresses in the Guinea savanna of West and Central Africa - Badu-Apraku, Baffour; Fakorede, M.A.B.; Menkir, A.; Kamara, A.Y.; Akanvou, L.; Chabi, Y. (2004)
Drought occurrence and striga hermonthica (Del.) Benth infestation are formidable maize (Zea mays L.) production constriants in the savanna zones of West and Central Africa (WCA). The West and Central Africa collaborative Maize Research Network (WECAMAN), in collaboration with the International Institute of Tropical Agriculture (IITA), Ibadan, Nigeria and the NARS of WCA has developed several drought and/or striga tolerant early maturing maize varieties for the savanna ecology. In 2000 and 2001, the performance of 17 early maturing varieties, subjected to induced drought stress and striga infeststion, was compared with their performance under a stress-free treatment. Relative to the stress-free treatment, mean grain yield was reduced by 53% under drought stress and by 42% under striga infestation. The stress increased anthesis-silking interval, drought also significantly reduced the number of ears per plant (EPP), the most important trait influencing grain yield under the two stresses. Five varieties (EV DT-W99 STR CO, 98 syn WEC, TZE-W pop X 1368 STR, AC 95 TZE Comp4 C3 F3 and RZE Comp3 C2)performed relatively well under the three treatments. Replication x genotype interaction sum of squares was large for all traits.